Anti-fog coating and preparation method thereof, and product
Through PECVD technology, a saturated chain monomer plasma polymerization with a specific structure is used to form an anti-fog coating, which solves the problems of solvent reaction and double bond residue in the prior art, and realizes an anti-fog coating with high hydrophilicity, excellent light transmittance and good wear resistance.
Patent Information
- Application Number
- CN202210319342.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-03-29
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2042-03-29
AI Technical Summary
The existing hydrophilic anti-fog coatings may react with the substrate during the preparation process, destroying the substrate structure, and the residual double bonds in the monomer may affect long-term performance.
Plasma enhanced chemical vapor deposition (PECVD) technology is used to form an anti-fog coating by contacting plasma containing saturated chain monomers with specific structures through the substrate to avoid double bond residues and improve hydrophilicity, light transmittance and wear resistance.
It realizes an anti-fog coating without double bond residue, with excellent hydrophilic properties, light transmittance and good wear resistance, and is suitable for hydrophilic anti-fog coating on transparent substrate surfaces.
Smart Images

Figure QLYQS_1 
Figure QLYQS_2 
Figure QLYQS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the field of plasma chemistry, and in particular to an anti-fog coating and a preparation method and product thereof. Background Art
[0002] Transparent materials (such as glass and plastic) are widely used in industrial and agricultural production, daily life and military fields, such as goggles, laser protective glasses, telescopes and lenses of various camera equipment, observation windows of various machines, sports diving goggles, bathroom glass, chemical or biological protective masks, vehicle windshields and rearview mirrors, explosive disposal and protection equipment, helmets, solar panels, observation windows of measuring instruments, glass covers, glass walls of greenhouses, etc. However, when we breathe out in winter, glasses will make us "see flowers in the fog"; in the cold winter, the fogging on the surface of the windshield will greatly affect our visibility and even cause accidents. The fogging problem brings many inconveniences to people's work and life, and the research and development of anti-fog technology and anti-fog materials have attracted much attention from the scientific and business communities.
[0003] Setting an anti-fog coating on the surface of transparent materials is a common anti-fog method. There are usually two types of anti-fog coatings. One is to form a hydrophilic surface on the surface of the transparent material, and water droplets spread into a film on the hydrophilic surface. The other is to form a hydrophobic surface on the surface of the transparent material, and water droplets roll down in beads on the hydrophobic surface. The disadvantage of the latter is that when a large amount of water vapor condenses rapidly, atomization will still occur. The former forms a uniform water film to eliminate the diffuse reflection of light and achieve the purpose of anti-fog.
[0004] At present, the technical improvement of hydrophilic anti-fog coating is mainly concentrated on the traditional liquid phase treatment method, including gel-sol method, layer-by-layer self-assembly method, free radical solution polymerization method, etc. These methods generally use spraying or spin coating to apply glue to the surface of the substrate, and then use heating or UV irradiation to cure. In the liquid phase treatment method, there is a disadvantage: the presence of solvents and reaction media may react with the substrate, destroy the substrate structure, and cause potential harm.
[0005] Plasma enhanced chemical vapor deposition (PECVD) is a chemical vapor deposition process that uses plasma generated by glow discharge at low pressure to activate monomers, generate highly active monomer radicals or ion fragments, and deposit them on the surface of the substrate to react and form a film. PECVD has the advantages of fast deposition rate, good film quality, fewer pinholes, and not easy to crack. It does not require liquid phase solvents during the reaction and will not damage the substrate. Therefore, the use of PECVD technology provides a better choice for the preparation of hydrophilic anti-fog coatings. The applicant's previous research, as disclosed in CN111501023A, found that by using acrylic monomers and PECVD to prepare hydrophilic coatings, a hydrophilic anti-fog coating can be prepared. On the one hand, the hydrophilic properties of the coating need to be improved; on the other hand, the monomers of the coating contain double bonds, and unstable double bonds will inevitably remain after the reaction, which may affect the performance of the coating during long-term use. Summary of the invention
[0006] The embodiments of the present disclosure provide an anti-fog coating, wherein the anti-fog coating has no residual double bonds and has excellent hydrophilicity, light transmittance, and good wear resistance. The specific scheme is as follows:
[0007] An anti-fog coating formed by contacting a substrate with a plasma containing a monomer of formula (1);
[0008] X 2 -RX 1 (1)
[0010] In formula (1), R is C 1 -C 30 Alkylene or C 1 -C 30 Substituted alkylene, X 1 and X 2 are independently selected from hydroxyl, amino or carboxyl; the substituent of the substituted alkylene group is hydroxyl, amino or carboxyl; the C 1 -C 30 Alkylene or C 1 -C 30 The carbon-carbon bonds of the substituted alkylene may or may not contain -NH-; and in formula (1), at most one of the amino group and the hydroxyl group may be connected to the same carbon atom.
[0011] Optionally, the monomer of formula (1) has a structure shown in formula (2),
[0012]
[0013] In formula (2), R 1 and R 2Each independently selected from C 1 -C 10 Alkylene or C 1 -C 10 A substituted alkylene group.
[0014] Optionally, the monomer of formula (1) has a structure shown in formula (3),
[0015]
[0016] In formula (3), X 3 and X 4 are independently selected from hydrogen, methyl, hydroxy, hydroxymethyl, amino or carboxyl; 1 is 0, 1, 2, 3, 4, 5, 6, 7, or 8; n 2 is 0, 1, 2, 3, 4, 5, 6, 7, or 8.
[0017] Optional, X 3 and X 4 are all hydrogen atoms, X 1 and X 2 are the same group.
[0018] Optionally, the R is C 1 -C 16 An alkylene group or a substituted alkylene group.
[0019] Optionally, the monomer of formula (1) has a structure shown in formula (4),
[0020]
[0021] In formula (4), X 5 and X 6 are independently selected from hydrogen, methyl, hydroxy, hydroxymethyl, amino or carboxyl; 3 is 0, 1, 2, 3, 4, 5, 6, 7, or 8.
[0022] Optional, X 5 and X 6 are all hydrogen atoms, X 1 and X 2 are the same group.
[0023] Optionally, the monomer of formula (1) is selected from monomers having structures shown in formula (1-1) to formula (1-48),
[0024]
[0025]
[0026]
[0027] Optionally, the substrate is an optical instrument, metal, ceramic, plastic, glass or electronic device.
[0028] Optionally, the optical instrument is a lens, a reflector or a lens.
[0029] Optionally, the substrate is a transparent material.
[0030] Optionally, the light transmittance of the anti-fog coating is above 90%.
[0031] Optionally, the water contact angle of the anti-fog coating is measured to be below 10°.
[0032] Optionally, after the anti-fog coating is rubbed 500 times with a dust-free cloth under a load of 1N, a water contact angle measured is below 10°.
[0033] The specific embodiment of the present disclosure also provides a method for preparing an anti-fog coating, which is used to prepare the anti-fog coating described above. The method for preparing the anti-fog coating comprises the following steps: providing a substrate, placing the substrate in a plasma reactor, passing the monomer vapor of the formula (1) into the plasma reactor, plasma discharge, and plasma polymerization on the surface of the substrate to form the anti-fog coating.
[0034] Optionally, before the monomer vapor of formula (1) is introduced into the plasma reactor, a plasma source gas is first introduced, and the plasma device is turned on for continuous discharge to pre-treat the surface of the substrate.
[0035] Optionally, the plasma source gas is one of helium, argon, nitrogen, oxygen, and hydrogen, or a mixture of several of them.
[0036] Optionally, the plasma discharge is a pulse plasma discharge, wherein the pulse power is 10W to 300W, the pulse duty cycle is 20% to 90%, and the discharge time of the pulse output is 30s to 36000s.
[0037] Optionally, the monomer of formula (1) is first added to an alcohol solvent to prepare a solution, which is then vaporized and introduced into a plasma reactor.
[0038] Optionally, the alcohol is one or more of methanol, ethanol or propanol.
[0039] A product, at least part of the surface of which has the above-mentioned anti-fog coating.
[0040] Compared with the prior art, the technical solution of the embodiment of the present disclosure has the following beneficial effects:
[0041] The anti-fog coating of the specific embodiment of the present disclosure is formed by plasma polymerization of a saturated chain monomer having at least hydroxyl, amino or carboxyl groups at both ends as shown in the substrate contact formula (1). The anti-fog coating formed by plasma polymerization of the monomer of the structure has excellent hydrophilicity, small color difference, excellent light transmittance, and good wear resistance. At the same time, since the monomer does not contain double bonds, the adverse effects on the performance of the anti-fog coating caused by the residual unstable double bonds in the anti-fog coating during long-term use are avoided. The anti-fog coating of the specific embodiment of the present disclosure is particularly suitable for use as a hydrophilic anti-fog coating on the surface of a transparent substrate. DETAILED DESCRIPTION
[0042] The inventors have found that the anti-fog coating formed by plasma polymerization of the saturated chain monomer shown in formula (1) has excellent hydrophilicity, light transmittance and good wear resistance. At the same time, since the monomer does not contain double bonds, the adverse effects on the performance of the anti-fog coating caused by the residual unstable double bonds in the anti-fog coating during long-term use are avoided. The anti-fog coating of the specific embodiment of the present disclosure is particularly suitable for use as a hydrophilic anti-fog coating on the surface of a transparent substrate.
[0043] The present disclosure provides an anti-fog coating according to the following specific embodiment, wherein the anti-fog coating is a plasma-polymerized coating formed by contacting a substrate with plasma containing a monomer of formula (1),
[0044] X 2 -RX 1 (1)
[0046] In formula (1), R is C 1 -C 30 Alkylene or substituted alkylene, X 1 and X 2 are independently selected from hydroxyl, amino or carboxyl; the substituent of the substituted alkylene group is hydroxyl, amino or carboxyl; the C 1 -C 30 The carbon-carbon bonds of the alkylene or substituted alkylene may or may not contain -NH-; and in formula (1), at most one of the amino group or the hydroxyl group may be connected to the same carbon atom.
[0047] The anti-fog coating of the specific embodiment of the present disclosure, X 1 and X 2 Independent of each other, X 1 and X 2 Can be the same group, such as X 1 and X 2 are hydroxyl, carboxyl or amino; X 1 and X 2 It can also be different groups, such as X1 is hydroxyl group, X 2 is a carboxyl group, such as X 1 is hydroxyl group, X 2 It is amino.
[0048] In the anti-fog coating of the specific embodiment of the present disclosure, at most one of the amino group or the hydroxyl group is connected to the same carbon atom, which means that the same carbon atom is only connected to one hydroxyl group, the same carbon atom is only connected to one amino group, or the same carbon atom has neither a hydroxyl group nor an amino group.
[0049] The anti-fog coating of the specific embodiment of the present disclosure, the C 1 -C 30 Alkylene or C 1 -C 30 The substituted alkylene group may be a linear or branched alkylene group, but considering better wear resistance and hydrophilicity, in some specific embodiments, the C 1 -C 30 Alkylene or C 1 -C 30 The substituted alkylene is a straight chain C 1 -C 30 An alkylene group or a substituted alkylene group.
[0050] The anti-fog coating of the specific embodiment of the present disclosure, in some specific embodiments, the C 1 -C 30 The alkylene or substituted alkylene has -NH- between carbon-carbon bonds.
[0051] In the anti-fog coating of the specific embodiment of the present disclosure, in some specific examples, the monomer of formula (1) has a structure shown in formula (2),
[0052]
[0053] In formula (2), R 1 and R 2 Each independently selected from C 1 -C 10 An alkylene group or a substituted alkylene group.
[0054] In the anti-fog coating of the specific embodiment of the present disclosure, in some specific examples, the monomer of formula (1) has a structure shown in formula (3),
[0055]
[0056] In formula (3), X 3 and X 4 are independently selected from hydrogen, methyl, hydroxy, hydroxymethyl, amino or carboxyl; 1is 0, 1, 2, 3, 4, 5, 6, 7, or 8; n 2 is 0, 1, 2, 3, 4, 5, 6, 7, or 8.
[0057] The anti-fog coating of the specific embodiment of the present disclosure, considering better hydrophilicity, in some specific embodiments, in formula (3), n 1 is 0, 1, or 2, n 2 Is 0, 1, or 2.
[0058] The anti-fog coating of the specific embodiment of the present disclosure, considering better hydrophilicity, in some specific embodiments, in formula (3), X 3 and X 4 are all hydrogen atoms, X 1 and X 2 It is simultaneously a hydroxyl group, an amino group, or a carboxyl group.
[0059] The anti-fog coating of the specific embodiment of the present disclosure, considering better hydrophilicity, in some specific embodiments, in formula (1), R is C 1 -C 16 An alkylene group or a substituted alkylene group.
[0060] The anti-fog coating of the specific embodiment of the present disclosure, in some specific embodiments, the C 1 -C 30 The alkylene group or the substituted alkylene group does not have -NH- between carbon-carbon bonds.
[0061] In the anti-fog coating of the specific embodiment of the present disclosure, in some specific examples, the monomer of formula (1) has a structure shown in formula (4),
[0062]
[0063] In formula (4), X 5 and X 6 are independently selected from hydrogen, methyl, hydroxy, hydroxymethyl, amino or carboxyl; 3 is 0, 1, 2, 3, 4, 5, 6, 7, or 8.
[0064] The anti-fog coating of the specific embodiment of the present disclosure, considering better hydrophilicity, in some specific embodiments, in formula (4), n 3 Is 0, 1, 2, 3, or 4.
[0065] The anti-fog coating of the specific embodiment of the present disclosure, considering better hydrophilicity, in some specific embodiments, in formula (4), X 5 and X 6 are all hydrogen atoms, X 1 and X 2It is simultaneously a hydroxyl group, an amino group, or a carboxyl group.
[0066] In some specific embodiments of the anti-fog coating of the specific embodiment of the present disclosure, the monomer of formula (1) is selected from monomers of structures shown in formula (1-1) to formula (1-48),
[0067]
[0068]
[0069]
[0070] In the anti-fog coating of the specific embodiment of the present disclosure, in some specific examples, the substituent of the substituted alkylene group is hydroxyl, amino or carboxyl.
[0071] In the anti-fog coating of the specific embodiment of the present disclosure, in some specific examples, the substrate is an optical instrument, metal, ceramic, plastic, glass or electronic device.
[0072] The anti-fog coating of the specific embodiments of the present disclosure, in some specific embodiments, the water contact angle of the anti-fog coating measured according to GB / T 30447-2013 is less than 10°, and water droplets can spread on the surface of the anti-fog coating and form a relatively uniform water film, thereby reducing diffuse reflection of light to achieve an anti-fog function. Therefore, in some specific embodiments, the anti-fog coating is particularly suitable for an anti-fog coating as a transparent material. For example, in some specific embodiments, the substrate is a lens of glasses, goggles, laser protective glasses, telescopes and lenses of various camera equipment, observation windows of various machines, sports diving goggles, bathroom glass, chemical or biological protective masks, vehicle windshields and rearview mirrors, explosive disposal and protection equipment, helmets, solar panels, observation windows of measuring instruments, glass covers, glass walls of greenhouses, etc.
[0073] The anti-fog coating of the specific embodiments of the present disclosure, in some specific embodiments, has excellent wear resistance and hydrophilicity. After the anti-fog coating is rubbed 500 times with a dust-free cloth at a load of 1N, the water contact angle measured according to GB / T30447-2013 is less than 10°.
[0074] In some specific embodiments of the anti-fog coating of the specific embodiments of the present disclosure, the light transmittance of the anti-fog coating is above 90%, which will not cause excessive impact on the light transmittance of the transparent substrate.
[0075] In the specific embodiments of the present disclosure, in some specific embodiments, the anti-fog coating is a plasma polymerized coating formed by the plasma of the monomer having the structure shown in formula (1). In other specific embodiments, due to specific practical needs, the anti-fog coating is a plasma polymerized coating formed by the plasma of the monomer having the structure shown in formula (1) and other monomers.
[0076] In some embodiments, the anti-fog coating of the specific embodiment of the present disclosure has a thickness of 1-1000 nm. In some embodiments, as an ultra-thin transparent nano coating, the thickness of the anti-fog coating is 1-100 nm, for example, 49 nm, 54 nm, 56 nm, 61 nm, 73 nm, 79 nm, 82 nm, 87 nm, 92 nm, 93 nm, 96 nm or 98 nm.
[0077] The specific embodiment of the present disclosure also provides a method for preparing the above-mentioned anti-fog coating, comprising the following steps: providing a substrate, placing the substrate in a plasma reactor, passing the monomer vapor of the formula (1) into the plasma reactor, plasma discharge, and plasma polymerization on the surface of the substrate to form the anti-fog coating.
[0078] The method for preparing the anti-fog coating according to the specific embodiment of the present disclosure is as described above with respect to the monomer and the substrate.
[0079] The preparation method of the anti-fog coating of the specific embodiment of the present disclosure is to further enhance the bonding strength between the plasma coating and the substrate. In some specific embodiments, before the monomer vapor is introduced, the substrate is pretreated with a continuous plasma source gas. The specific pretreatment method is, for example, in an atmosphere of a plasma source gas, a plasma discharge power of 20 to 500 W is used, the discharge method is continuous, and the discharge time is 10s to 3600s.
[0080] In some specific embodiments of the method for preparing the anti-fog coating of the specific embodiments of the present disclosure, monomer vapor is introduced simultaneously with the introduction of plasma source gas to perform pretreatment and coating pre-deposition.
[0081] In the method for preparing the anti-fog coating according to the specific embodiments of the present disclosure, in some specific embodiments, the plasma source gas introduced is one of helium, argon, nitrogen, oxygen, and hydrogen, or a mixture of several of them.
[0082] In the method for preparing the anti-fog coating of the specific embodiment of the present disclosure, in some specific embodiments, the plasma of the monomer is a plasma excited in a pulsed manner, and the monomer flow rate is 10 to 500 μL / min, for example, 10 μL / min, 50 μL / min, 100 μL / min, 150 μL / min, 200 μL / min, 300 μL / min or 400 μL / min, etc.
[0083] In the method for preparing the anti-fog coating of the specific embodiment of the present disclosure, in some specific embodiments, the temperature in the cavity is controlled at 20°C-80°C, for example, it can be 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C or 80°C, etc.; the pressure in the cavity is below 1000 mTorr, further below 500 mTorr, and further below 100 mTorr.
[0084] In the preparation method of the anti-fog coating of the specific embodiment of the present disclosure, in some specific embodiments, the vaporization temperature of the monomer is 50°C to 200°C, and specifically can be 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, etc., and the vaporization occurs under vacuum conditions, and the pulse plasma is generated by applying a pulse voltage discharge, wherein the pulse The pulse power is 10W to 300W, and specifically can be 10W, 20W, 30W, 40W, 50W, 70W, 80W, 100W, 120W, 140W, 160W, 180W, 190W, 200W, 210W, 220W, 230W, 240W, 250W, 260W, 270W, 280W, 290W or 300W, etc. In some specific embodiments, the pulse power is 30W to 100W; the pulse duty cycle is 0.1% ~90%, specifically for example, it can be 0.1%, 0.5%, 1%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85% or 90%, etc. In some specific embodiments, considering better hydrophilicity, the pulse duty cycle is 20% to 90%, further the pulse duty cycle is 40% to 80%, further the pulse duty cycle is 45% to 75%; The plasma discharge time of the pulse output is 30s to 36000s, and can be, for example, 100s, 500s, 1000s, 1800s, 2000s, 1000s, 2000s, 3000s, 3600s, 4000s, 5000s, 6000s, 7000s, 7200s, 10800s, 14400s, 18000s, 21600s, 25200s, 28800s, 32400s or 36000s, etc.
[0085] In the preparation method of the anti-fog coating of the specific embodiment of the present disclosure, in some specific embodiments, the plasma discharge mode can be various existing discharge modes, for example, electrodeless discharge (such as radio frequency inductively coupled discharge, microwave discharge), single electrode discharge (such as corona discharge, plasma jet formed by monopole discharge), double electrode discharge (such as dielectric barrier discharge, bare electrode radio frequency glow discharge) and multi-electrode discharge (such as discharge using a floating electrode as the third electrode).
[0086] In the method for preparing the anti-fog coating of the specific embodiment of the present disclosure, in some specific embodiments, the monomer of formula (1) is first added to an alcohol solvent to prepare a solution, and then vaporized into a plasma reactor, which can reduce the vaporization temperature of the monomer and is more conducive to the vaporization of the monomer. In some specific embodiments, the alcohol is one or more of methanol, ethanol or propanol.
[0087] The specific embodiments of the present disclosure also provide a product, wherein at least a portion of the surface of the product has any of the above-mentioned anti-fog coatings. In some specific embodiments, the above-mentioned anti-fog coating is deposited on a portion of the surface or the entire surface of the device.
[0088] The present disclosure is further described below through specific embodiments.
[0089] Example
[0090] Test Method Description
[0091] Coating thickness test: Use the American Filmetrics F20-UV-film thickness measuring instrument for testing.
[0092] Coating water contact angle: tested according to GB / T 30447-2013 standard.
[0093] Coating transmittance and color difference: calculated according to GB11186.3-1989 standard, tested using a spectrophotometer, ΔE in the test results represents color difference, T represents transmittance; L, a, and b represent the three color channels in the Lab color model. L represents brightness, and its value range is [0, 100], representing from pure black to pure white; a represents the range from red to green, and its value range is [127, -128]; b represents the range from yellow to blue, and its value range is [127, -128].
[0094] Friction performance test: Use a reciprocating abrasion machine to rub with a dust-free cloth 500 times under a load of 1N to test the change in water contact angle before and after friction.
[0095] Example 1
[0096] A substrate transparent glass plate (length: 75 mm, width: 26 mm, thickness: 1 mm) was placed in a 500L plasma vacuum reaction chamber, and the reaction chamber was continuously evacuated to a vacuum degree of 80 mTorr. The internal temperature of the chamber was 45°C, and helium was introduced at a flow rate of 40 sccm;
[0097] The chamber pressure was maintained at 80 mTorr, the helium flow rate was maintained at 40 sccm, and the RF plasma discharge was turned on. The RF energy output mode was continuous discharge, the discharge time was 30 s, and the discharge power was 300 W.
[0098] Then, a monomer having a structure shown in formula (1-6) was introduced, the monomer flow rate was 50 μL / min, the monomer vaporization temperature was 90° C., the cavity pressure was maintained at 80 mTorr, the helium flow rate was maintained at 40 sccm, the RF plasma discharge was turned on, the RF energy output mode was pulsed, the discharge power was 40 W, the pulse duty cycle was 75%, the pulse frequency was 50 Hz, and the discharge time was 3600 s, to form a coating on the surface of the transparent glass plate;
[0099]
[0100] After the coating preparation was completed, air was introduced to restore the reaction chamber to normal pressure, the chamber was opened, and the transparent glass plate was taken out to test the coating thickness, transmittance, chromaticity, water contact angle and friction resistance. The test results are listed in Table 1 below.
[0101] Example 2
[0102] The monomer of the structure represented by formula (1-6) in Example 1 is replaced by a monomer of the structure represented by the following formula (1-4). The vaporization temperature of the monomer of the structure represented by formula (1-4) is 90°C. The other processes are consistent with Example 1. The prepared coating is tested for thickness, transmittance, chromaticity, water contact angle and friction resistance. The test results are listed in Table 1 below.
[0103]
[0104] Example 3
[0105] The monomer of the structure represented by formula (1-6) in Example 1 is replaced by a monomer of the structure represented by the following formula (1-19). The vaporization temperature of the monomer of the structure represented by formula (1-19) is 110°C. The other processes are consistent with Example 1. The prepared coating is tested for thickness, transmittance, chromaticity, water contact angle and friction resistance. The test results are listed in Table 1 below.
[0106]
[0107] Example 4
[0108] The transparent glass plate substrate in Example 1 was replaced with a transparent PC (polycarbonate) plate substrate. The other processes were consistent with Example 1. The prepared coating was tested for thickness, transmittance, chromaticity, water contact angle and friction resistance. The test results are listed in Table 1 below.
[0109] Example 5
[0110] The transparent glass plate substrate in Example 2 was replaced by a transparent PC (polycarbonate) plate substrate. The other processes were consistent with Example 2. The prepared coating was tested for thickness, transmittance, chromaticity, water contact angle and friction resistance. The test results are listed in Table 1 below.
[0111] Example 6
[0112] The transparent glass plate substrate in Example 3 was replaced by a transparent PC (polycarbonate) plate substrate. The other processes were consistent with Example 3. The prepared coating was tested for thickness, transmittance, chromaticity, water contact angle and friction resistance. The test results are listed in Table 1 below.
[0113] Example 7
[0114] A substrate transparent glass plate (length: 75 mm, width: 26 mm, thickness: 1 mm) was placed in a 500L plasma vacuum reaction chamber, and the reaction chamber was continuously evacuated to a vacuum degree of 80 mTorr. The internal temperature of the chamber was 45°C, and helium was introduced at a flow rate of 40 sccm;
[0115] The chamber pressure was maintained at 80 mTorr, the helium flow rate was maintained at 40 sccm, and the RF plasma discharge was turned on. The RF energy output mode was continuous discharge, the discharge time was 30 s, and the discharge power was 300 W.
[0116] Then, 20 g of a monomer having a structure represented by the following formula (1-43) and 100 mL of ethanol were prepared into a solution, and the solution was vaporized at 150° C. and then introduced into a reaction chamber at a flow rate of 150 μL / min, the chamber pressure was maintained at 80 mTorr, the helium flow rate was maintained at 160 sccm, and radio frequency plasma discharge was started, the radio frequency energy output mode was pulsed, the discharge power was 40 W, the pulse frequency was 50 Hz, the pulse duty cycle was 45%, and the discharge time was 3600 s, to form a coating on the surface of a transparent glass plate;
[0117]
[0118] After the coating preparation was completed, air was introduced to restore the reaction chamber to normal pressure, the chamber was opened, and the transparent glass plate was taken out to test the thickness, transmittance, chromaticity, water contact angle and friction resistance of the coating. The test results are listed in Table 1.
[0119] Example 8
[0120] The monomer of the structure represented by formula (1-43) in Example 7 was replaced by a monomer of the structure represented by the following formula (1-21). The other processes were consistent with Example 7. The thickness, transmittance, chromaticity, water contact angle and friction resistance of the prepared coating were tested. The test results are listed in Table 1 below.
[0121]
[0122] Example 9
[0123] The transparent glass plate substrate in Example 7 was replaced by a transparent PC (polycarbonate) plate substrate. The other processes were consistent with Example 7. The prepared coating was tested for thickness, transmittance, chromaticity, water contact angle and friction resistance. The test results are listed in Table 1 below.
[0124] Example 10
[0125] The transparent glass plate substrate in Example 8 was replaced with a transparent PC (polycarbonate) plate substrate. The other processes were consistent with Example 8. The prepared coating was tested for thickness, transmittance, chromaticity, water contact angle and friction resistance. The test results are listed in Table 1 below.
[0126] Comparative Example 1
[0127] The monomer of the structure represented by formula (1-6) in Example 1 is replaced by a hexanol monomer of the structure represented by the following formula (5), the vaporization temperature of the hexanol monomer of the structure represented by formula (5) is 110°C, and the other processes are consistent with Example 1. The thickness, transmittance, chromaticity, water contact angle and friction resistance of the prepared coating are tested, and the test results are listed in Table 1.
[0128]
[0129] Comparative Example 2
[0130] The monomer of the structure represented by formula (1-6) in Example 4 is replaced by the caproic acid monomer of the structure represented by the following formula (6). The vaporization temperature of the caproic acid monomer of the structure represented by formula (6) is 110°C. The other processes are consistent with Example 5. The thickness, transmittance, chromaticity, water contact angle and friction resistance of the prepared coating are tested. The test results are listed in Table 1.
[0131]
[0132] Table 1 Performance test results of Examples 1-10 and Comparative Examples 1-2
[0133]
[0134] According to the results in Table 1, the coatings of Examples 1 to 10 before friction all have a water contact angle of 5° to 6°, which is much lower than the water contact angles of 77° and 72° of the coatings of Comparative Examples 1 and 2, which further indicates that the coatings formed by plasma polymerization of the monomers having two hydrophilic groups in Examples 1 to 10 have better hydrophilicity and anti-fogging properties than the monomers of Comparative Examples 1 and 2 having one hydrophilic group.
[0135] At the same time, according to the results in Table 1, the coatings formed by plasma polymerization of saturated chain monomers having hydroxyl, amino or carboxyl groups at both ends of Examples 1 to 10 have good wear resistance. After rubbing 500 times with a dust-free cloth under a load of 1N using a reciprocating abrasion machine, the water contact angle does not change by more than 4°, and the color difference of the coating is very small, between 0.5 and 0.6, and the light transmittance of the coating is very good. Compared with Comparative Example 1, Comparative Example 2 and the transparent glass plate and PC plate without deposited coating, it has higher light transmittance and has a certain degree of anti-reflection effect.
[0136] In addition, it can be seen from Examples 7 to 10 that for monomers with a higher boiling point, the boiling point of the monomer can be lowered by adding ethanol, and the coating finally obtained also has excellent hydrophilicity and wear resistance, small color difference, and excellent light transmittance.
[0137] Although the disclosure is disclosed as above, the disclosure is not limited thereto. Any person skilled in the art can make various changes and modifications without departing from the spirit and scope of the disclosure, so the protection scope of the disclosure should be based on the scope defined by the claims.
Claims
1. An anti-fog coating, characterized in that: The anti-fog coating is formed by contacting a substrate with a plasma containing a monomer of formula (1); ; In formula (1), R is C1-C 30 Alkylene or C1-C 30 A substituted alkylene group, X1 and X2 are independently selected from hydroxyl, amino or carboxyl; the monomer does not include ethylene glycol; The substituent of the substituted alkylene group is hydroxyl, amino or carboxyl; C1-C 30 Alkylene or C1-C 30 The carbon-carbon bonds of the substituted alkylene may or may not have -NH-; In formula (1), at most one of an amino group or a hydroxyl group is connected to the same carbon atom.
2. The anti-fog coating according to claim 1, characterized in that The monomer of formula (1) has a structure shown in formula (2), ; In formula (2), R1 and R2 are independently selected from C1-C 10 Alkylene or C1-C 10 A substituted alkylene group.
3. The anti-fog coating according to claim 2, characterized in that: The monomer of formula (1) has a structure shown in formula (3), ; In formula (3), X3 and X4 are independently selected from hydrogen atom, methyl group, hydroxyl group, hydroxymethyl group, amino group or carboxyl group; n1 is 0, 1, 2, 3, 4, 5, 6, 7 or 8; n2 is 0, 1, 2, 3, 4, 5, 6, 7 or 8.
4. The anti-fog coating according to claim 3, characterized in that: X3 and X4 are both hydrogen atoms, and X1 and X2 are the same group.
5. The anti-fog coating according to claim 1, characterized in that: The R is C1-C 16 An alkylene group or a substituted alkylene group.
6. The anti-fog coating according to claim 5, characterized in that: The monomer of formula (1) has a structure shown in formula (4), ; In formula (4), X5 and X6 are independently selected from hydrogen atom, methyl group, hydroxyl group, hydroxymethyl group, amino group or carboxyl group; n3 is 0, 1, 2, 3, 4, 5, 6, 7 or 8.
7. The anti-fog coating according to claim 6, characterized in that: X5 and X6 are both hydrogen atoms, and X1 and X2 are the same group.
8. The anti-fog coating according to claim 1, characterized in that: The monomer of formula (1) is selected from monomers having structures represented by formula (1-1), formula (1-2), formula (1-4) to formula (1-48), ; ; ; 。 9. The anti-fog coating according to claim 1, characterized in that: The substrate is an optical instrument, metal, ceramic, plastic, glass or electronic equipment.
10. The anti-fog coating according to claim 9, characterized in that: The optical instrument is a lens, a reflector or a mirror.
11. The anti-fog coating according to claim 9, characterized in that: The substrate is a transparent material.
12. The anti-fog coating according to claim 1, characterized in that: The light transmittance of the anti-fog coating is above 90%.
13. The anti-fog coating according to claim 1, characterized in that: The water contact angle of the anti-fog coating is measured to be below 10°.
14. The anti-fog coating according to claim 13, characterized in that: After the anti-fog coating was rubbed 500 times with a dust-free cloth under a load of 1N, a water contact angle measured was below 10°.
15. A method for preparing an anti-fog coating according to any one of claims 1 to 14, characterized in that: The following steps are involved: A substrate is provided, and the substrate is placed in a plasma reactor. The monomer vapor of the formula (1) is introduced into the plasma reactor, and plasma discharge is performed to form the anti-fog coating on the surface of the substrate through plasma polymerization.
16. The method for preparing the anti-fog coating according to claim 15, characterized in that: Before the monomer vapor of formula (1) is introduced into the plasma reactor, a plasma source gas is first introduced, and the plasma device is turned on for continuous discharge to pre-treat the surface of the substrate.
17. The method for preparing the anti-fog coating according to claim 16, characterized in that: The plasma source gas is one of helium, argon, nitrogen, oxygen and hydrogen, or a mixture of several of them.
18. The method for preparing the anti-fog coating according to claim 15, characterized in that: The plasma discharge is a pulse plasma discharge, wherein the pulse power is 10W to 300W, the pulse duty cycle is 20% to 90%, and the discharge time of the pulse output is 30s to 36000s.
19. The method for preparing the anti-fog coating according to claim 15, characterized in that: Firstly, the monomer of formula (1) is added into an alcohol solvent to prepare a solution, which is then vaporized and introduced into a plasma reactor.
20. The method for preparing the anti-fog coating according to claim 19, characterized in that: The alcohol is one or more of methanol, ethanol or propanol.
21. A product, characterized in that At least part of the surface of the product has the anti-fog coating according to any one of claims 1 to 14.
Citation Information
Patent Citations
Hydrophilic anti-fog film, preparation method and application of hydrophilic anti-fog film and product with hydrophilic anti-fog film
CN111501023A
Nano coating preparation method and antibiosis nano coating prepared by nano coating
CN103160786A
Long-acting optical anti-fogging film and production method thereof
CN106240115A
Method for preparing antifogging plastic film by surface coating process
CN1775834A